2011
DOI: 10.7852/ijie.2011.23.1.107
|View full text |Cite
|
Sign up to set email alerts
|

Light and Electron Microscopic Study on the Development of Nosema Bombyics Naegeli in the Midgut of Silkworm Bombyx Mori L.

Abstract: Infection effect of Nosema bombycis on the midgut of silkworm Bombyx mori and subsequent appearance of spores and the performance of larvae was studied. Autopsy of larvae showed white pustules on the surface of midgut at 5 days of post infection (pi). At later stage, important organs like midgut, silk gland and gonads reduced in size and all these organs showed white pustules. Light microscope observation of pustules revealed enormous spores. Spore multiplication was at a faster rate in young larvae. Infection… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 4 publications
0
4
0
Order By: Relevance
“…Some studies show that chemical treatments performed long before mulberry plantations were established in a given place resulted in long-term accumulation of toxins in the soil. The effects of those accumulations affected larval mortality up to 36 months after sprayings (Jyothi et al 2019). Even small amounts of pesticides can have a significant impact on different aspects of development and rearing performance of silkworms.…”
Section: Discussionmentioning
confidence: 99%
“…Some studies show that chemical treatments performed long before mulberry plantations were established in a given place resulted in long-term accumulation of toxins in the soil. The effects of those accumulations affected larval mortality up to 36 months after sprayings (Jyothi et al 2019). Even small amounts of pesticides can have a significant impact on different aspects of development and rearing performance of silkworms.…”
Section: Discussionmentioning
confidence: 99%
“…This result similar to Rao et al (2004) that suggests that at a dose of 10 7 spores ml -1 mortality can reach more than 50% after infection. While studies of Jyothi and Patil (2011) showed that fourth instar mortality was 86% at a concentration of 1×10 6 spores larva -1 , infectivity can reach 90% at a concentration 1.52×10 6 spores ml -1 . …”
Section: Disease Occurrencementioning
confidence: 98%
“…This result similar to Rao et al (2004) that suggests that at a dose of 10 7 spores ml -1 mortality can reach more than 50% after infection. While studies of Jyothi and Patil (2011) showed that fourth instar mortality was 86% at a concentration of 1×10 6 spores larva -1 , infectivity can reach 90% at a concentration 1.52×10 6 spores ml -1 (Chakrabarty et al, 2012).…”
Section: Disease Occurrencementioning
confidence: 99%
“…The new external symptoms were observed after day 10 DAI and mortality of larvae increased in both inoculation instar 3 or 4. Histopathological study by Jyothi and Patil (2011) shows the midgut has formed sporoblast phase on the third day after infection. Hossain et al (2012), sporo plasma gradually increased in size and developed into meronts 24-48 hrs after inoculation.…”
Section: Disease Occurrencementioning
confidence: 99%